2018
DOI: 10.1002/vms3.103
|View full text |Cite
|
Sign up to set email alerts
|

Serological, cultural and molecular evidence of Brucella melitensis infection in goats in Al Jabal Al Akhdar, Sultanate of Oman

Abstract: Brucellosis, one of the most common zoonotic diseases and has significant public health and economic importance worldwide. Few studies and reports have been performed to estimate the true prevalence of animal brucellosis in the Sultanate of Oman; however, no incidence of the disease was previously reported in Al Jabal Al Akhdar. The purpose of this study was to investigate the prevalence of brucellosis in goats in eight villages in Al Jebal Al Akhdar, Sultanate of Oman, namely: Al Aqaieb, Al Helailat, Al Ghila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…First, the data were collected through passive public health surveillance. With regard to the untypical symptoms of some human brucellosis and inaccessible health facilities for some patients, data may be influenced by under-reporting, laboratory misdiagnosis and incomplete information 29 30. Second, as human brucellosis is a zoonotic disease which is affected by many factors, such as the density of livestock, meat yield, slaughter amount and environment, a dynamic model including the abovementioned factors needs to be taken into account for brucellosis transmission and prediction, but these data could not be obtained in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…First, the data were collected through passive public health surveillance. With regard to the untypical symptoms of some human brucellosis and inaccessible health facilities for some patients, data may be influenced by under-reporting, laboratory misdiagnosis and incomplete information 29 30. Second, as human brucellosis is a zoonotic disease which is affected by many factors, such as the density of livestock, meat yield, slaughter amount and environment, a dynamic model including the abovementioned factors needs to be taken into account for brucellosis transmission and prediction, but these data could not be obtained in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…The overall brucellosis prevalence seropositivity in the study area was 0.48% by RBT and i-ELISA, which is lower than that found in Al-Ahsa KSA which was 1.1% [ 41 ], Alkamil, KSA 5.88% [ 10 ], Abu Dhabi Emirate 8.3% [ 42 ], Oman 2.4%, (Dhofar) 8.6%, Northern governorates 0.97%, Al Aqaieb 24%, and Al Helailat 40%. While in Al Ghilayil, Al Qasha’e, Da’anAlhamra, Al Sarah, Hail Al Hedap, and Shnoot are free from brucellosis [ 13 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary can refer acidified antigens in RPBT usually produce prozoning phenomena (false positive result), [ 44 ]. Hence, i- ELISA has been evaluated for many years for their better sensitivity to detect anti- Brucella antibodies in all species especially small ruminant, several studies reported that i-ELISA is more sensitive than conventional tests [ 13 ] assessed the indirect ELISA efficacy in comparison with CFT and RBPT on sera from B. melitensis infected ewes. Indirect ELISA can be a useful screening tool and could be used alone or in addition to RBT.…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is the most common zoonotic disease in Oman (Idris et al, 1993, El-Amin et al, 2001, MOH, Oman, 2014, Ministry of Health, Oman, 2017. Brucella melitensis is widely circulated in camels, goats, sheep, and cattle in Oman [MOH, Oman, 2017;El Tahir and Nair, 2011;El Tahir et al, 2018; National center for Statistics and information). Nationally, the brucellosis incidence rate declined from 20/ 100,000 population (371 cases) in 1992 to 8/100,000 population (376 cases) in 2017 (Table 1).…”
Section: Brucellosismentioning
confidence: 99%
“…Eighty percent (1145) of the cases were male. Sixty-three percent (908) of the cases occurred due to ingestion of unpasteurized milk or fresh unpasteurized cheese from infected goats or sheep, while 83% had a history of direct contact with animals, mainly cattle (MOH, 2014;El-Amin et al, 2001;Idris et al, 1993;El Tahir and Nair, 2011;El Tahir et al, 2018; National center for Statistics and information; Al-Rawahi, 2015).…”
Section: Brucellosismentioning
confidence: 99%